Are accessible software accountable?: A commentary. Issue 1 (2nd January 2022) - Goldberg, Mary; Karimi, Hassan; Jordan, J. Bern; Lazar, Jonathan
ABSTRACT: Accessible software is increasingly important as the incidence of disability continues to increase and the population ages globally, ensuring people are not left behind in the digital revolution. Likewise, there is increased interest in ensuring software is accountable such that it is clear about the information it uses and the actions that it takes. While there have been some agreed-upon definitions for accessible, interpretable, and transparent software, accountable software lacks a universal definition and methodology. We argue that for a software to be accountable, it must also be accessible, interpretable, and transparent, and provide a methodology for developing accountable software.